A review on synthesis and modification of dolomite-based adsorbent for heavy metal removal / Nur Natasha Alia Mohd Zawawi - Mohd Zawawi, Nur Natasha Alia (2024)
The utilization of dolomite-based adsorbents for heavy metal removal in aqueous environments stands as a promising avenue in addressing water pollution challenges. This review explores the distinctive attributes of dolomite, such as its natural abundance, cost-effectiveness, and favorable surface characteristics, which position it as a superior adsorbent compared to conventional materials. The synthesis methods, including calcination and chemical treatments are critically examined for their impact on the structural, morphological, and surface properties of dolomite-based adsorbents. Furthermore, the study investigates innovative modification approaches, incorporating advanced nanomaterials and eco-friendly agents, to modify the surface chemistry and reactivity of dolomite, thereby improving its adsorption efficiency. Emphasizing the need for comprehensive evaluations, the study discusses scalability, recyclability, and long-term performance assessments of dolomite-based adsorbents in real-world water treatment scenarios. This research not only contributes to advancing the understanding of dolomite’s efficacy as an adsorbent but also provides valuable insights into the optimization of synthesis and modification techniques for sustainable and effective heavy metal removal.